Complexidade, aprendizagem e medo: bases biológicas das emoções e sentimentos e a problemática educacional - Wekerlin Filho, Duglas (2007)
This work aims to produce an updated theoretical reference of the biological bases of emotions, feelings and fear so that the issues related to violence in school environments can be better understood, allowing the proposal of recommendations in order to make violence become less frequent and reach less those living in these environments. This work brings data related to different forms of violence that occur in public and private schools of basic education and college education in one case, as well as data related to the consequences of such violence on the mental health of teachers. In order to collect the data, a direct observation research was conducted in the form of the interview of a teacher who has been working in the field of University Education for 37 years. Besides, a bibliographic research was done about complexity, dialogue, organization, systems, emergencies, emotions, feelings, fears and school violence. Aiming to complement the research, a documental research was conducted based on four programs presented by Radio B-SP about school violence at schools in Sao Paulo and Rio de Janeiro. This work gives a social contribution in the sense that conflicting issues in the mediation of learning can be approached in different school environments and that people who live in them can feel welcomed, can develop their potential as human beings and can learn more and better